THE MOTIVATION AND MEANING OF VISITING SACRED PLACES FOR INDONESIAN MUSLIMS - Baidun, Akhmad; Latifa, Rena; Muchtar, Desi Yustari; Rahmah, Muthia; Nyhof, Melanie (Psikis : Jurnal Psikologi Islami, 2023)
Muslims often visit places that are considered sacred or have spiritual significance in their lives. This study aims to (1) identify what places are considered sacred places and are often visited by Indonesian Muslims, (2) identify what motivations underlie the trip to visit these sacred places, (3) identify what meanings are obtained from activities to visit sacred places, (4) examine the effect of motivation on the meaning of visiting sacred places. The participant of this research is 225 Indonesian Muslims. Construct validity was analyzed using Confirmatory Factor Analysis through LISREL 8. 7. Data analysis was performed using multiple linear regression with SPSS. The results showed that (1) there are several places that are considered as sacred places and often visited by Muslims, namely the cemeteries of family, ancestor, ‘wali’ and ‘kyai’, important figures, grand mosque in each part of the country, Mecca/Medina and Islamic historical places, (2) There are several motivations in visiting the sacred place, namely: religious motive, spiritual motive, new experience motive, cultural motive, outdoor and natural motive, motivation to break from routine, motivation to meet people and visit other places, and motivation to fulfill promises or traditions, (3) there are 2 meanings obtained from visiting sacred places, namely: vertical self-transcendence and horizontal self-transcendence, (4) vertical self-transcendence is influenced by religious and spiritual motivation, while horizontal self-transcendence influenced by religious motives, outdoor and natural motives, break from a routine motive.